Broadband highly efficient nonlinear optical processes in on-chip integrated lithium niobate microdisk resonators of Q-factor above 108. (15th December 2021) - Gao, Renhong; Zhang, Haisu; Bo, Fang; Fang, Wei; Hao, Zhenzhong; Yao, Ni; Lin, Jintian; Guan, Jianglin; Deng, Li; Wang, Min; Qiao, Lingling; Cheng, Ya
Abstract: Microresonators of ultrahigh quality ( Q ) factors represent a crucial type of photonic devices aiming at ultra-high spectral resolution, ultra-high sensitivity to the environmental perturbations, and efficient nonlinear wavelength conversions at low threshold pump powers. Lithium niobate on insulator (LNOI) microdisks of high Q factors are particularly attractive due to its large second-order nonlinear coefficient and strong electro-optic property. In this letter, we break through the long standing bottleneck in achieving the Q factors of LNOI microresonators beyond 10 8, which approaches the intrinsic material absorption limit of lithium niobate (LN). The ultra-high Q factors give rise to a rich family of nonlinear optical phenomena from optical parametric oscillation (OPO) to harmonics generation with unprecedented characteristics including ultra-low pump threshold, high wavelength conversion efficiency, and ultra-broad operation bandwidth. Specifically, the threshold of OPO is measured to be only 19.6 μ W, and the absolute conversion efficiency observed in the second harmonic generation reaches 23%. The record-breaking performances of the on-chip ultra-high Q LNOI microresonators will have profound implication for both photonic research and industry.